Dinamika Dan Resolusi Konflik Ala Budaya Organisasi Nahdlatul Ulama - Jauhari, Sidik (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2026)
Internal conflicts within religious organizations are deeply rooted in communication practices, social identity formation, and organizational culture. This study examines the dynamics and resolution processes of conflict within the PCNU Blitar Regency, employing a communication and organizational culture perspective. The conflict originated from uncertainty regarding the issuance of the management decree by the PBNU, coupled with instructions for re-election, which triggered internal tension, group polarization, and disputes over leadership legitimacy. Using a descriptive qualitative case study approach, data were collected through in-depth interviews, non-participant observation, and document analysis. The study utilizes Linda L. Putnam’s communicative conflict management theory as its primary analytical framework. Findings reveal that the conflict was exacerbated by weak organizational communication, lack of transparency, and a reliance on unstructured informal communication. To resolve the conflict, PCNU Blitar combined informal mechanisms—rooted in silaturahim and tabayyun—with formal structural forums based on Nahdlatul Ulama’s core values (tawassuth, tasamuh, tawazun, and i’tidal). However, resolution effectiveness remains hindered by a rigid hierarchical culture and resistance from certain internal actors. This research emphasizes the necessity of transparent, participatory communication as the foundation for sustainable religious organizational governance.